Russian aviation industry and First World War challenges - Pavlo Tkachuk; Andrij Kharuk; Ihor Soliar; Lilia Skorych (Історія науки і техніки, 2022)
The purpose of this study is to highlight the peculiarities of the development of the Russian aviation industry during the First World War. The focus is on analyzing production programs and matching their quantitative and qualitative parameters to war requirements. The main methods used in our work are problem-chronological, used to describe the state of the Russian aviation industry, and comparative, used to compare the level of development of the Russian aviation industry with other countries that participated in the First World War. General scientific methods have also found their application ‒ primarily, analysis and synthesis. The research resulted in the following conclusions: First World War became a challenge for Russian industry that was in the developing stage, including aviation industry. Needs of the front demanded for increase in plane productions that was a complex task for Russia, taking into account its economic backwardness. Aviation industry, being represented by several big (in the scope of Russia) enterprises, demonstrated a dynamic of growth. For the war period the plane production capacity had increased only in 3 times while in Germany – in 10 times and in France and Great Britain the growth was much bigger. Leading enterprises of aviation industry, such as factory of Duks, Liebiediev, Anatra, Shchetinin – mainly copied foreign samples (French, and sometimes German). Efforts to establish the production of original samples were a complete failure. The most known example is fighter “Illia Muromets” that was a leading one in 1914 but became old-fashioned till 1917. Aviation engine production was also narrow and was far beyond plane production. Enormous investments made in the development existed and building of new enterprises of planes and aviation engines production in 1916‒1917 did not show any results, none of the enterprises started the production. We have analyzed some of these failures – building of Anatra factory in Simferopol and Matias factory in Berdiansk, and aero-motors factories Anatra in Simferopol and Deka in Aleksandrovsk. State police on controlling aviation industry based on providing subsidies and preferential loan, turned to be ineffective – it was vanished by basic purchasing prices that did not count on inflation. That is why Russian aviation industry appeared to be unable to face and respond to war challenges. Production plans of leading Russian aviation factories as well as qualitative and quantitative parameters of products have been analyzed in the article.